2015
DOI: 10.3402/fnr.v59.29018
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofHibiscus sabdariffaextract on high fat diet–induced obesity and liver damage in hamsters

Abstract: BackgroundObesity is a chronic metabolic disorder associated with an increase in adipogenesis and often accompanied with fatty liver disease.ObjectiveIn this study, we investigated the anti-obesity effects of Hibiscus sabdariffa water extract (HSE) in vivo.MethodEight-weeks-old male mice were divided into six groups (n=8 per group) and were fed either normal feed, a high fat diet (HFD), HFD supplemented with different concentrations of HSE, or HFD supplemented with anthocyanin. After 10 weeks of feeding, all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 55 publications
5
47
0
1
Order By: Relevance
“…basic standard diet gained weight in the first two weeks. This is in agreement with the trend reported by Huang [19] who fed Hamster rats, standard laboratory diet in their experiment for 10 weeks and established evidence of weight gain. The exhibition of weight gain in the first week among the rats on basic standard diet could have been due to accommodation of excess lipids and glucose in the adipose tissues and muscle as a normal storage site in form of glycogen.…”
Section: Discussionsupporting
confidence: 82%
“…basic standard diet gained weight in the first two weeks. This is in agreement with the trend reported by Huang [19] who fed Hamster rats, standard laboratory diet in their experiment for 10 weeks and established evidence of weight gain. The exhibition of weight gain in the first week among the rats on basic standard diet could have been due to accommodation of excess lipids and glucose in the adipose tissues and muscle as a normal storage site in form of glycogen.…”
Section: Discussionsupporting
confidence: 82%
“…For example, neither AST nor ALT levels were significantly elevated by high‐fat diet feeding for 10 weeks in Outbred CD‐1 Mice . While ALT and AST levels increased in hamsters fed with high‐fat diet for same 10 weeks . Studies on EC also indicated that it could significantly reduce TG at a very lower dose (1 mg/kg BW) in rats , but failed to do so at a much higher dose (0.01 mol/kg BW) in mice .…”
Section: Discussionmentioning
confidence: 97%
“…HSE and anthocyanins regulated total body weight and visceral fat, reduced serum cholesterol and triglyceride levels, protected against oxidation-associated damage in liver by regulating a liver antioxidant enzyme (paraoxonase 1), and also reduced liver damage biomarkers ALT and AST [146]. …”
Section: Effects Of Bioactive Compounds From the Morinda Citrifolimentioning
confidence: 99%